Relationship between Surfactant and Population of Heterotrophic Bacteria in Estuary of Dumai River Dumai City Riau Province - Aqil Fikar Rivai; Syahril Nedi; Irwan Effendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on April 2017. Sampling was conducted in estuary of Dumai River, Dumai City, Riau Province. A study aims to determine the relationship between concentration of surfactant and population of heterotrophic bacteria in the estuary waters of Dumai River Dumai City Riau Province. Sampling was done at 6 sampling points (stations). The analysis of surfactant concentration was conducted at the Chemical Laboratory of the Sea and the total analysis of heterotrophic bacteria at the Marine Microbiology Laboratory of Department of Marine Science Faculty of Fisheries and Marine University of Riau, Pekanbaru. The results showed that the highest concentration of surfactant was found at Station 5 (0.8538 mg / l) and the lowest at Station 1 (0.2025 mg / l). Then, the logarithm of the highest average total colony was found at Station 1 (6.18 cells / ml) while the lowest at Station 5 (5.66 cells / ml). The correlation concentration models of surfactant with the total colony using regression was negative correlation Y = 6.3745 - 0.7882 (X), R2 = 0.8622, r = 0.9285 showed that the value of surfactant concentration (X) increased by 1 unit will decrease the total of colony (Y) was 0,7882 cells/ml, with the effect of surfactant to bacteria equal 85% and the level of closeness of the relationship was 93%.Kata Kunci : Surfactant, Heterotrophic bacteria, Estuary of Dumai River